Penyuluhan dan Sosialisasi Hukum: Gratifikasi Dalam Perspektif Hukum di SMA Swasta APIPSU Medan - Dahris Siregar; Cut Rafyqa Fadhilah; Jamaluddin Mahasari; Maria Fransiska Ndruru; Albert Christianwan Laoli; Wezdi Damai Lase; Primasali Laia (Abdimas Universal, 2024)
Legal counseling and socialization activities for APIPSU Medan High School students are gratification from a legal perspective. This exercise aims to educate pupils about the law and inspire them to take part in forming moral character and abstaining from immoral behaviour. To achieve this goal, in addition, it called on the Indonesian government to take firmer measures to reduce the level of corruption. To accomplish this task, the resulting material on corruption crimes is presented. Next, students talk and ask questions to the speaker. In general, the purpose of this extension is to identify two things intended to determine the level of understanding and sensitivity of students to law enforcement in handling gratuities that occur in their surrounding environment and point out other options that researchers use to increase students' awareness and understanding of law enforcement in handling gratuities around them. This activity goes well, anti-corruption learning can help students develop good and honest character. Although the country's economy is not directly affected by anti-corruption education, a sustainable one can lower the level of corruption in the Indonesian government and society.